CIRCULATING LEVELS OF 25-HYDROXYVITAMIN D AND TESTOSTERONEDURING THE RUTTING AND NON-RUTTING PERIODS IN MOROCCANDROMEDARY CAMELS (CAMELUS DROMEDARIUS) - Khasmi, M. El; Riad, Fouad; Safwate, Abdallah; Tahri, El hassane; Farh , Mohamed; Abbadi, Najia El; Coxam, Véronique; Fay, Bernard (Emirates Journal of Food and Agriculture, 2017)
The camel is largely known to be a seasonal breeder, thus, in the male camel, the breeding activity maximizes during the rutting period (winter and spring seasons) but ceases completely during the non-rutting period (summer and autumn). Plasma vitamin D3 concentrations showed significant seasonal variations; the purpose of this study was to investigate a possible role of vitamin D in the sexual activity in Moroccan dromedary camels by evaluating the variation in plasma vitamin D, calcium, and phosphorus concentrations in relation to those of testosterone during these two periods. Blood samples were collected from 14 adult male camels aged 5-8 years, slaughtered during March (n=7) and September (n=7) at the Tit-Mellil Municipality slaughterhouse. All animals were clinically healthy and blood samples were taken at 06 h AM into heparinized tubes. In the work reported here, our results showed that plasma levels of 25-hydroxyvitamin D were significantly higher and those of testosterone were significantly lower in the non-rutting animals when compared to the rutting ones (p<0.005). While, the plasma levels of calcium and inorganic phosphorus showed no seasonal variation. Based on the values obtained in this investigation, vitamin D does not appear to contribute directly or indirectly to camel steroidogenesis. Further studies, from the one hand of an eventual relationship between T and other parameters such as thyroid hormones and corticoids, and from the another one of testing the vitamin D action on rutting behavior are needed in camels.